2009 IEEE Intelligent Vehicles Symposium 2009
DOI: 10.1109/ivs.2009.5164351
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and emotion in autonomous cars

Abstract: In order to increase the acceptance of vehicles that drive (partly) autonomously, it seems advantageous that the driving style of autonomous cars is human-like. Furthermore, the acceptance of autonomous cars is believed to be increased when their actions and current state becomes more transparent to the passengers. These aspects can be tackled by implementing emotions to an autonomous car which allows a situation specific adaption of driving functions and vehicle dynamics. In this work, the emotions are modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…These findings lend themselves to the development of current level 3 automated vehicles where the driver is required to be available for occasional control of the vehicle. Regarding the current lack of feedback for driver reassurance as highlighted by Kraus et al [16], we have shown that an auditory display containing Earcons modulated by Pitch and Timbre is also an effective solution for maintaining awareness to the actions of an automated vehicle. This opens up new possibilities for auditory displays and highlights the use of Earcons as an effective alternative for information presentation in automated vehicles.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…These findings lend themselves to the development of current level 3 automated vehicles where the driver is required to be available for occasional control of the vehicle. Regarding the current lack of feedback for driver reassurance as highlighted by Kraus et al [16], we have shown that an auditory display containing Earcons modulated by Pitch and Timbre is also an effective solution for maintaining awareness to the actions of an automated vehicle. This opens up new possibilities for auditory displays and highlights the use of Earcons as an effective alternative for information presentation in automated vehicles.…”
mentioning
confidence: 84%
“…As automated vehicles currently do not provide sufficient feedback relating to the primary driving task, drivers have no assurance that an automated vehicle has understood and can cope with upcoming traffic situations [16]. To address this we conducted two user evaluations to investigate auditory displays in automated vehicles using different types of sound cues related to the primary driving sounds: acceleration, deceleration/braking, gear changing and indicating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have not only improved mechanical efficiency with the development of engine management systems, electronic ignition and fuel-injection systems but occupant safety has been increased via the addition of anti-lock braking systems (ABS), improved traction control and power assisted steering (PAS) [18]. It is also interesting to point out that the inclusion of computerised systems not only improves road safety and vehicle efficiency, but they can also create a more enjoyable driving experience [13].…”
Section: Context and Motivationmentioning
confidence: 99%